Structural Change and Labor Market Integration: Evidence from Ukraine - Oliskevych, Marianna; Lukianenko, Iryna (International Journal of Economics and Financial Issues, 2017)
This paper aims to research of unevenness and imbalances problems on the labor markets in Ukrainian regions. Indexes of structural changes in regional employment on different economic activities are evaluated as well as sectoral diversification indexes of employment in different regions. Comparison of employment structure in Ukraine and the EU countries is made. Econometric models describing changes in the level of employment in the region as a whole and separately in agriculture and industry are estimated for regional panel data for 2004–2014 years. The impact of an initial employment, index of sectoral employment diversification in the region, geographical attractiveness index, the initial level of regional economic integration with the European countries and the CIS are estimated as well as their changes over the last six years. Advantages of European integration for Ukraine and the negative impact of integration with CIS countries on the labor market are detected. Keywords: labor market, integration, employment. JEL Classifications: E24, Ð¡50